Room temperature fuel cell type hydrogen sensor based on pd metalene nanosheet / carbon fiber composite electrode material and preparation method thereof
Patent Information
- Application Number
- CN202611274538.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明旨在克服现有室温燃料电池型氢气传感器中贵金属催化剂原子利用率低、易团聚失活、长期稳定性差的技术瓶颈,提供了一种基于超薄Pd金属烯纳米片/碳纤维复合电极材料的室温燃料电池型氢气传感器及其制备方法
[0024](1)本发明采用低温羰基辅助溶剂热还原法制备超薄二维Pd金属烯纳米片,并通过浸渍负载法与碳纤维复合,工艺简单、条件温和、重复性好;Pd金属烯纳米片的二维超薄一体化结构使绝大多数Pd原子均暴露于表面,从材料本征层面解决了传统纳米颗粒催化剂内部原子浪费的问题,有效提高了贵金属原子利用率,显著降低了贵金属用量与制造成本;
Smart Images

Figure CN123008947A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas sensor technology, specifically relating to a room temperature fuel cell hydrogen sensor based on Pd metallene nanosheet / carbon fiber composite electrode material and its preparation method. Background Technology
[0002] Fuel cell-based hydrogen sensors can operate at room temperature without external bias, offering significant advantages such as intrinsic safety, zero power consumption, simple structure, and low cost, demonstrating immense application potential in hydrogen detection. The core component of this type of sensor is the membrane electrode assembly (MEA), primarily composed of a sensitive electrode material and a solid polymer electrolyte membrane. The sensitive electrode material typically contains a noble metal catalyst and its support, which work synergistically to act as both a catalytic active center and an electron conduction channel, directly determining the sensor's sensitivity, response speed, and long-term stability. Therefore, the selection of electrode materials is the bridge connecting the material's microstructure and the device's macroscopic performance. A well-designed electrode structure can synergistically optimize catalytic activity and electron transport efficiency, thereby endowing the sensor with high sensitivity, rapid response, and long-term reliability—the key to realizing the practical application of room-temperature fuel cell-based hydrogen sensors.
[0003] However, the noble metal catalysts commonly used in this type of sensor are usually in the form of nanoparticles. While they can provide high initial catalytic activity, they face many limitations in practical applications. Nanoparticles have low atomic utilization, with a large number of internal atoms unable to participate in surface reactions, resulting in a waste of precious metals. Simultaneously, due to their high surface energy, nanoparticles are prone to aggregation and Ostwald ripening during long-term operation, leading to a continuous decrease in electrochemical active area and a reduction in sensor sensitivity. Furthermore, precious metals themselves are expensive, and it is difficult to precisely control particle size and distribution, thus affecting device consistency and mass production. Therefore, breakthroughs are urgently needed through the structural design of novel catalytic materials; this is a crucial challenge that must be overcome to move fuel cell-type hydrogen sensors from the laboratory to production applications.
[0004] To address the low utilization rate of precious metal atoms in sensors, some studies have attempted to improve this. Some research employs MOF-derived alloy strategies, utilizing the spatial confinement effect of MOF precursors to suppress metal agglomeration and achieve uniform dispersion of precious metals at the atomic scale, thus obtaining higher catalytic activity with extremely low precious metal usage. Other studies explore non-precious metal alternative catalysts, such as using transition metal oxides like MnO2 to completely replace precious metals like Pt and Au, fundamentally eliminating dependence on precious metals. Still other studies develop novel supports and structural designs, utilizing highly conductive supports like MXene or constructing atomically dispersed catalysts to optimize the dispersion state and electronic structure of precious metals, thereby improving their utilization efficiency. Summary of the Invention
[0005] This invention aims to overcome the technical bottlenecks of low atom utilization, easy agglomeration and deactivation, and poor long-term stability of noble metal catalysts in existing room-temperature fuel cell hydrogen sensors. It provides a room-temperature fuel cell hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode material and its preparation method. In the following text, the ultrathin Pd metallene nanosheet / carbon fiber composite electrode material will be abbreviated as Pdene / CF composite electrode material.
[0006] This invention utilizes ultrathin two-dimensional Pd metalloene nanosheets as the catalytic active phase and carbon fibers as the support to prepare Pdene / CF composite electrode materials via an impregnation loading method. These materials are then used as the active components to fabricate sensitive and reference electrodes, ultimately constructing a room-temperature fuel cell-type hydrogen sensor. On one hand, the integrated two-dimensional ultrathin structure of the Pd metalloene nanosheets provides a high electrochemical active area, with the vast majority of Pd atoms exposed on the surface, unlike zero-dimensional nanoparticles where a large number of internal atoms are "buried." This fundamentally avoids the problem of internal atom waste commonly found in traditional nanoparticle catalysts, ensuring sufficient active sites even with extremely low noble metal loadings and significantly improving the atomic utilization rate of noble metals. Simultaneously, this structure effectively suppresses the common nanoparticle aggregation and Ostwald ripening, endowing the sensor with excellent long-term stability. On the other hand, the highly exposed Pd active sites and the excellent electronic conduction of the carbon fiber support synergistically reduce the charge transfer resistance of the sensor, effectively increasing the area of the three-phase interface reaction zone within the catalytic layer, and significantly improving the sensor's response value and sensitivity.
[0007] This invention discloses a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metalloene nanosheet / carbon fiber composite electrode material. From top to bottom, it comprises a coaxially arranged and fixedly encapsulated gas diffusion cap, a membrane electrode assembly, a gasket, and a water tank. The membrane electrode assembly, from top to bottom, consists of a sensitive electrode, a Nafion membrane, and a reference electrode. The active components of both the sensitive and reference electrodes are the Pdene / CF composite electrode material described in this invention. This invention includes steps such as preparing ultrathin Pd metalloene nanosheets using a low-temperature carbonyl-assisted solvothermal reduction method, preparing the Pdene / CF composite electrode material using an impregnation method, preparing the membrane electrode assembly using a hot-pressing method, and coaxial assembly.
[0008] The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode, as described in this invention, comprises the following steps:
[0009] (1) Palladium acetylacetonate (Pd(acac)2) and tungsten hexacarbonyl (W(CO)6) were dispersed in a mixed solvent consisting of N,N-dimethylformamide (DMF) and acetic acid; the mixture was sonicated for 30-60 min to fully dissolve the solid and obtain the precursor solution.
[0010] The mass ratio of Pd(acac)2 to W(CO)6 is 1:2~4, and the volume ratio of DMF to acetic acid is 2~6:1; in the mixed solvent, the concentration of Pd(acac)2 is 0.001~0.005 mol / L, and the concentration of W(CO)6 is 0.0006~0.002 mol / L; the ultrasonic treatment temperature is <25 ℃.
[0011] (2) The precursor solution obtained in step (1) is transferred to the reaction vessel, and the product Pd metal olefin nanosheets are obtained after the reaction.
[0012] The reaction conditions were to maintain the temperature at 50-90 ℃ for 2-4 h.
[0013] (3) The product obtained in step (2) is centrifuged and washed 5 to 10 times with anhydrous ethanol at a speed of 7000 to 9000 r / min, and the time for each centrifugation and washing is 5 to 10 min; then, the washed product is redispersed in anhydrous ethanol and then placed in a cell disruptor for ultrasonic dispersion treatment to obtain Pd metal olefin nanosheet suspension.
[0014] The ultrasonic power is 350~400 W and the ultrasonic time is 20~40 min.
[0015] (4) Disperse the pretreated carbon fibers in anhydrous ethanol, sonicate for 8-15 minutes, and continue stirring. During stirring, add the Pd metallene nanosheet suspension obtained in step (3) dropwise. Then continue stirring for 1-3 hours to ensure that the Pd metallene nanosheets are uniformly attached to the surface of the carbon fibers. Finally, dry in a vacuum oven at 50-70 °C for 10-12 hours. After grinding, obtain the Pdene / CF composite electrode material. The mass fraction of Pd metallene nanosheets in the Pdene / CF composite electrode material is 5-30 wt%.
[0016] The process involves sequentially bathing carbon fiber (CF) in a 3%–9% (v / v) H2O2 aqueous solution, a 0.3–0.6 M H2SO4 aqueous solution, and deionized water at 70–90 °C for 0.5–1.5 h, followed by vacuum drying at 60–80 °C for 6–12 h to obtain pretreated carbon fiber.
[0017] (5) Add 10-30 mg of the Pdene / CF composite electrode material obtained in step (4) to a dispersant consisting of 100-120 μL of ethylene glycol, 200-240 μL of 5% Nafion solution and 400-480 μL of deionized water, and sonicate it to disperse it evenly to obtain a catalytic slurry; uniformly coat the catalytic slurry onto the surface of two flat polytetrafluoroethylene films, and dry them to obtain a sensitive electrode and a reference electrode with a Pdene / CF composite electrode material layer on the surface. The thickness of the Pdene / CF composite electrode material layer is 100-300 μm.
[0018] (6) Place the sensitive electrode and reference electrode obtained in step (5) on both sides of the pretreated Nafion membrane and bond them together by hot pressing process, wherein the Pdene / CF composite electrode material layer on the sensitive electrode and the reference electrode are both facing the Nafion membrane; after naturally cooling to room temperature, remove the polytetrafluoroethylene membrane on both sides of the Nafion membrane to obtain the membrane electrode assembly.
[0019] The hot pressing process is carried out at a temperature of 85~95 ℃, a pressure of 7~10 MPa, and a time of 60~150 s;
[0020] The pretreatment steps of the Nafion membrane are as follows: The Nafion membrane is pretreated sequentially in a 3-9% (v / v) H2O2 aqueous solution, a 0.3-0.6 M H2SO4 aqueous solution, and deionized water in a water bath at 70-90 °C for 0.5-1.5 h, and then dried.
[0021] (7) Assemble the gas diffusion cap, the membrane electrode assembly obtained in step (6), the isolation pad and the water tank coaxially from top to bottom, and after fixing and sealing, a room temperature fuel cell hydrogen sensor based on ultrathin Pd metallene nanosheet / carbon fiber composite electrode is obtained.
[0022] The membrane electrode assembly has a thickness of 370~790 μm and a diameter of 5~20 mm; the gas diffusion cap has a thickness of 1~5 mm; the isolation gasket has a thickness of 0.2~1 mm; the water tank has a height of 10~60 mm; the diameter of the isolation gasket is similar to the diameter of the membrane electrode assembly, and both are smaller than the inner diameter of the water tank but larger than the outer diameter of the gas diffusion cap; the gas diffusion cap is made of stainless steel and has vent holes on its surface; the isolation gasket is made of stainless steel and has a micropore with a diameter of 0.5~3 mm in its center; the water tank is made of stainless steel and has an integrally formed annular boss near the top of its inner wall, on which the isolation gasket is placed.
[0023] The room-temperature fuel cell-type hydrogen sensor based on a Pd metallene nanosheet / carbon fiber composite electrode described in this invention has the following advantages:
[0024] (1) The present invention uses a low-temperature carbonyl-assisted solvothermal reduction method to prepare ultrathin two-dimensional Pd metal olefin nanosheets, and combines them with carbon fibers by impregnation loading method. The process is simple, mild and reproducible. The two-dimensional ultrathin integrated structure of Pd metal olefin nanosheets exposes most of the Pd atoms on the surface, which solves the problem of atomic waste inside traditional nanoparticle catalysts from the intrinsic material level, effectively improves the utilization rate of precious metal atoms, and significantly reduces the amount of precious metals used and the manufacturing cost.
[0025] (2) This invention utilizes the integrated two-dimensional ultrathin structure of Pd metal olefin nanosheets to naturally maximize the exposure of active sites without the need for external templates or carrier confinement, effectively increasing the electrochemical active area and significantly reducing the charge transfer resistance, thereby greatly improving the response value and sensitivity of the sensor. At the same time, the integrated structure effectively inhibits the aggregation and Ostwald ripening of nanoparticles, giving the sensor excellent long-term stability, and realizing high sensitivity, fast response recovery, low cost and long lifespan detection of hydrogen.
[0026] (3) The present invention adopts a device structure in which the membrane electrode assembly, gas diffusion cap, isolation gasket and water storage tank are coaxially arranged and fixedly packaged from top to bottom. The device process is simple, low cost and small size. The sensor can work at room temperature without external bias voltage, has intrinsic safety characteristics, is suitable for mass production, has good practical value in the field of hydrogen energy safety monitoring, and provides a promising technical solution for the application of low power consumption and integrated room temperature hydrogen sensing system. Attached Figure Description
[0027] Figure 1 The transmission electron microscope (TEM) and atomic force microscope (AFM) images of the Pd metalloene nanosheets provided in Example 1 of this invention correspond to, respectively Figure 1 (a) and Figure 1 (b);
[0028] Figure 2 TEM image and energy-dispersive X-ray spectroscopy (EDS) image of the Pdene / CF composite electrode material provided in Embodiment 1 of the present invention;
[0029] Figure 3 X-ray diffraction (XRD) patterns of Pdene / CF composite electrode materials with different mass fractions provided in Examples 1 and 2 of the present invention;
[0030] Figure 4This is a schematic diagram of the structure of the fuel cell hydrogen sensor provided in Embodiment 1 of the present invention. The sensor is composed of a gas diffusion cap, a membrane electrode assembly, a gasket, and a water tank arranged coaxially from top to bottom and fixedly packaged. The sensor is tested in different gas environments, and the air inside and outside the diffusion hole is in a dynamic flow state.
[0031] Figure 5 (a) The response current curves of sensors based on different mass fractions (5 wt%, 10 wt%, 20 wt%, 30 wt%) of Pdene / CF composite electrode materials provided in Examples 1 and 2 of the present invention and the sensor based on 20 wt% PdNPs / CF composite electrode material provided in Comparative Example 1 to 3000 ppm H2. The "current I" shown on the vertical axis is the current value of the sensor's external circuit directly measured by the "it" mode of the electrochemical workstation. Figure 5 (b) Comparison of the fitting curves of the response current and the corresponding H2 concentration of the sensors based on different mass fractions (5 wt%, 10 wt%, 20 wt%, 30 wt%) of Pdene / CF composite electrode materials provided in Embodiments 1 and 2 of the present invention and the sensor based on 20 wt% PdNPs / CF composite electrode material provided in Comparative Example 1. The "response current ΔI" shown on the vertical axis is defined as ΔI = Ig - Ia, where Ig and Ia are the current values of the sensor's external circuit measured in the target gas and air environments, respectively.
[0032] Figure 6 (a) The concentration-response current curves of the sensor based on 20 wt% Pdene / CF composite electrode material provided in Example 1 of the present invention and the sensor based on 20 wt% PdNPs / CF composite electrode material provided in Comparative Example 1 for 300~7500 ppm H2. The "current I" shown on the vertical axis is the current value of the sensor external circuit directly measured by the "it" mode of the electrochemical workstation. Figure 6 (b) is the response recovery time test curve of the sensor based on 20 wt% Pdene / CF composite electrode material to 3000 ppm H2 provided in Example 1 of the present invention. The "current I" shown on the vertical axis is the current value of the sensor's external circuit directly measured by the "it" mode of the electrochemical workstation.
[0033] Figure 7 (a) is the repeatability test curve of the sensor based on 20 wt% Pdene / CF composite electrode material provided in Example 1 of the present invention. The "current I" shown on the vertical axis is the current value of the sensor external circuit directly measured by the "it" mode of the electrochemical workstation. Figure 7(b) The selectivity test curves of the sensor based on 20 wt% Pdene / CF composite electrode material provided in Example 1 of the present invention for 100 ppm H2, NO2, CO, NH3, CH4, C2H6O and 5 ppm H2S. The "response current ΔI" shown on the vertical axis is defined as ΔI = Ig - Ia, where Ig and Ia are the current values of the sensor's external circuit measured in the target gas and air environments, respectively. Figure 7 (c) The long-term stability test curves of the sensor based on 20 wt% Pdene / CF composite electrode material provided in Example 1 of the present invention and the sensor based on 20 wt% PdNPs / CF composite electrode material provided in Comparative Example 1 are shown. The "response current ΔI" shown on the vertical axis is defined as ΔI = Ig - Ia, where Ig and Ia are the current values of the sensor's external circuit measured in the target gas and air environments, respectively. Detailed Implementation
[0034] Example 1: Preparation of 20 wt% Pdene / CF composite electrode material and sensor assembly
[0035] This embodiment provides a specific method for preparing Pdene / CF composite electrode materials and assembling fuel cell-type hydrogen sensors based on a low-temperature carbonyl-assisted solvothermal reduction method.
[0036] (1) Synthesis of Pd metalloene nanosheets:
[0037] 16 mL of N,N-dimethylformamide (DMF) and 4 mL of acetic acid were measured using a graduated cylinder. 20 mg of palladium acetylacetone (Pd(acac)2) and 40 mg of tungsten hexacarbonyl (W(CO)6) were weighed and dissolved in DMF and acetic acid, respectively. The mixture was sonicated at 20 °C for 30 minutes. After the solid was fully dissolved, it was transferred to a 50 mL reaction vessel and kept at 70 °C for 3 hours to obtain black colloidal Pd metallene nanosheets. The obtained black colloidal Pd metallene nanosheets were washed with anhydrous ethanol at 8000 r / min for 8 min each time. After centrifugation and washing, the supernatant was discarded and the nanosheets were redispersed in anhydrous ethanol. This centrifugation and washing process was repeated 7 times to remove unreacted Pd(acac)2 precursor, W(CO)6 decomposition products, and residual organic solvents. The washed product was redispersed in 20 mL of anhydrous ethanol and then subjected to ultrasonic dispersion in a cell disruptor at a power of 360 W for 30 min to fully exfoliate and disperse the aggregated Pd metallene nanosheets, resulting in a uniform and stable Pd metallene nanosheet suspension with a concentration of approximately 0.25 mg / mL.
[0038] (2) Preparation of Pdene / CF composite electrode material:
[0039] Carbon fibers were sequentially treated in a 5% (v / v) H2O2 aqueous solution, a 0.5M H2SO4 aqueous solution, and deionized water at 80°C for 1 h. After removal, they were vacuum dried at 60°C for 9 h to obtain pretreated carbon fibers.
[0040] 80 mg of pretreated carbon fibers were weighed and dispersed in 50 mL of anhydrous ethanol. The mixture was then ultrasonically treated for 15 min at 200 W to ensure thorough dispersion. The resulting carbon fiber dispersion was then placed on a magnetic stirrer and stirred continuously at 400 r / min. 80 mL of the Pd metal ene nanosheet suspension obtained in step (1) was added dropwise to the mixture using a pipette, with a dropping rate of 1 mL / s while maintaining stirring. After the addition was complete, stirring was continued at room temperature for 2 h to allow the Pd metal ene nanosheets to adhere uniformly to the carbon fiber surface. Subsequently, the mixture was transferred to a petri dish and dried in a vacuum drying oven at 60 ℃ for 12 h at a vacuum degree of -0.1 MPa. After drying, the product was removed and gently ground and dispersed using an agate mortar to obtain 100 mg of Pdene / CF composite electrode material powder, in which the mass fraction of Pd metal ene nanosheets was 20 wt%.
[0041] (3) Weigh 30 mg of the Pdene / CF composite electrode material powder prepared above, add it to a dispersant composed of 50 μL ethylene glycol, 100 μL 5 wt% Nafion solution and 200 μL deionized water, and sonicate for 30 min to form a uniformly dispersed catalytic slurry. Use a blade coating method to uniformly coat 100 μL of the above catalytic slurry onto the surface of two flat polytetrafluoroethylene (PTFE) films, and dry them in a 90 ℃ oven for 15 min. After drying, a sensitive electrode and a reference electrode with a Pdene / CF composite electrode material layer on the surface are obtained. The thickness of the Pdene / CF composite electrode material layer is 150 μm.
[0042] (4) Preparation of membrane electrode assembly: Take a Nafion 117 proton exchange membrane (a type of Nafion membrane with a thickness of 180 μm), and pretreat it sequentially in a 5% (v / v) H2O2 aqueous solution, a 0.5 M H2SO4 aqueous solution, and deionized water at 80 °C for 1 hour. After drying, place the sensitive electrode and reference electrode obtained in step (3) on both sides of the pretreated Nafion 117 proton exchange membrane with the Pdene / CF composite electrode material layers facing each other. After alignment, place them in a hot press and hot press them at 90 °C and 8 MPa for 90 seconds. After naturally cooling to room temperature, remove the PTFE membranes on both sides of the Nafion 117 proton exchange membrane to obtain the membrane electrode assembly (thickness of 480 μm). Finally, press it into a disc with a diameter of 11 mm for later use.
[0043] (5) Sensor Packaging: The sensor is assembled as follows: A stainless steel gas diffusion cap with a thickness of 3 mm and an outer diameter of 10 mm is placed on the top layer. The side wall of the gas diffusion cap has a vent hole with a diameter of 1 mm. The membrane electrode assembly disc obtained in step (4) is placed below the gas diffusion cap, with the sensitive electrode surface facing the gas diffusion cap. External air or hydrogen diffuses into the gas diffusion cap through the vent hole on the side wall and reacts with the Pdene / CF composite electrode material layer on the surface of the sensitive electrode. A stainless steel isolation pad with a thickness of 0.5 mm and an outer diameter of 11 mm is placed below the membrane electrode assembly. The isolation pad has a micropore with a diameter of 1 mm in the center. A water tank containing deionized water (which provides a high humidity environment for the Nafion membrane to ensure its high proton conductivity) and an integrally formed annular boss near the top of the inner wall is placed at the bottom. The water tank has an outer diameter of 12 mm and an inner diameter of 11 mm. mm; After pressing the gas diffusion cap, membrane electrode assembly, isolation gasket and water tank in sequence along the axial direction, hot melt adhesive is used to mechanically fix and seal the joint between the water tank and the gas diffusion cap, thus obtaining the room temperature fuel cell hydrogen sensor based on Pd metallene nanosheet / carbon fiber electrode material.
[0044] (1) Sensor testing: The packaged sensor is installed in a test fixture, which consists of a plastic shell, a spring, an upper copper plate, and a lower copper plate. After installation, the upper surface of the gas diffusion cap of the sensor is in close contact with the upper copper plate, and the bottom surface of the water tank is in elastic contact with the lower copper plate through the spring. The upper copper plate is connected to the counter electrode and reference electrode interface of the electrochemical workstation through wires, and the lower copper plate is connected to the working electrode interface of the electrochemical workstation through wires, thus forming a complete electrochemical test circuit (i.e., external circuit). The electrochemical workstation adopts a constant potential current detection mode, and the applied potential is 0 V (this type of sensor generates current by gaining and losing electrons in the external circuit through the redox reaction between the cathode and anode, so no external bias voltage is required). The sensor performance is tested by static gas mixing method, that is, the assembled sensor is placed in a sealed test chamber, clean air is first introduced, and after the baseline of the sensor output current is stable, a quantitative amount of H2 standard gas is injected into the test chamber to reach a preset concentration (e.g., 300~7500 ppm), and the change curve of the sensor's external circuit response current over time is recorded. Once the response current reaches saturation, clean air is introduced again to restore the sensor to its initial baseline. The above steps are repeated to obtain the sensor's response data to different concentrations of H2.
[0045] Example 2: Preparation of Pdene / CF composite electrode materials with different mass fractions and sensor assembly
[0046] The preparation process of this embodiment is basically the same as that of Example 1, except that the amount of Pd metalene nanosheet suspension added is different. Specifically, in step (2), Pd metalene nanosheet suspension of corresponding volumes (20 mL, 40 mL, and 120 mL) is added dropwise to carbon fiber dispersion according to the mass percentage of Pd metalene nanosheets of 5%, 10%, and 30%, respectively. After stirring and mixing, it is dried under vacuum to obtain Pdene / CF composite electrode materials of different mass fractions (denoted as 5 wt% Pdene / CF, 10 wt% Pdene / CF, and 30 wt% Pdene / CF, respectively). The remaining steps, including the fabrication of the sensitive electrode and the reference electrode, the preparation of the membrane electrode assembly, and the packaging and testing of the sensor, are the same as those in Example 1.
[0047] Comparative Example 1: Preparation and Sensor Assembly of 20 wt% PdNPs / CF Electrode Material
[0048] This comparative example uses a traditional chemical reduction method to prepare Pd nanoparticles, in order to verify the significant advantages of the ultrathin two-dimensional Pd metallene nanosheets of this invention in improving the utilization rate of noble metals. The synthesis method of 20 wt% PdNPs / CF electrode material is as follows:
[0049] (1) Weigh 74.8 mg of potassium chloropalladium (K2PdCl6) and 80 mg of pretreated carbon fiber and place them in a reaction vessel. Add 165.8 mg of trisodium citrate (C6H5O7Na3·2H2O) as a stabilizer. The molar ratio of trisodium citrate to potassium chloropalladium is 3:1. Add 50 mL of deionized water to the mixture and sonicate for 30 min to ensure that the components are fully dispersed and uniform.
[0050] (2) Under rapid stirring conditions, 25 mL of 0.5 M sodium borohydride (NaBH4) ice-water solution was added dropwise to the suspension obtained in step (1) as a reducing agent; then the mixture was placed in an 80 ℃ water bath and stirred at 500 r / min for 2 h to allow Pd to react. 4+ Fully reduced to zero-valent Pd nanoparticles;
[0051] (3) After the reaction is complete, the product obtained in step (2) is washed repeatedly with deionized water 5 times, and solid-liquid separation is carried out by vacuum filtration to remove unreacted raw materials and by-products; then the washed product is placed in a vacuum oven at 60 °C and dried for 12 h to obtain 100 mg of 20 wt% PdNPs / CF composite electrode material.
[0052] The 20 wt% PdNPs / CF composite electrode material prepared in Comparative Example 1 was used to fabricate a fuel cell H2 sensor using the same membrane electrode preparation process and sensor packaging method as steps (3)-(5) in Example 1, for performance comparison testing.
[0053] like Figure 1 As shown in (a), the Pd metallene nanosheets exhibit a graphene-like ultrathin two-dimensional nanosheet morphology. The nanosheets have an irregular, curved, wrinkled structure with a lateral dimension of 200–600 nm. Figure 1 As shown in (b), the thickness of the Pd metallene nanosheets was measured to be 0.8~2 nm, indicating that they consist of several atomic layers.
[0054] like Figure 2 As shown in (a), metal Pd with a two-dimensional nanosheet morphology is uniformly and densely loaded on the surface of carbon fiber, exhibiting a "sheet-fiber" encapsulation attachment, which can reduce the charge transfer resistance to a certain extent and maximize the exposure of its active sites. Figure 2 (b) to (d) are planar EDS plots of Pdene / CF, where, Figure 2 (b) shows the overall elemental distribution map, clearly illustrating the distribution of Pd and C elements. Pd is uniformly distributed across the carbon fiber surface, and its distribution area highly overlaps with that of C, indicating that the impregnation method successfully achieved uniform loading of Pd metalloolefins onto the carbon fiber support. Figure 2(c) is a distribution map of carbon (C) element. It can be seen that carbon element uniformly covers the entire field of view, corresponding to the carbon fiber substrate; Figure 2 (d) shows the distribution of palladium (Pd) element. It can be seen that Pd element is distributed in a uniform sheet or dot pattern, indicating that Pd metal olefin nanosheets are uniformly and densely distributed on the carbon fiber surface without obvious agglomeration.
[0055] like Figure 3 As shown, the characteristic peak of CF in the sample matches the carbon standard card (JCPDS:75–0444) at 2θ = 26.3°. The characteristic peak of Pd in the sample matches the standard card (JCPDS:87–0643) at 2θ = 39.9°, 46.4°, and 67.7°, representing the (111), (200), and (220) planes of metallic Pd, respectively. Furthermore, the peak value of the Pd characteristic peak gradually increases with the increase of Pd loading.
[0056] like Figure 4 As shown, the names of each part are: vent 1, gas diffusion cap 2, stainless steel isolation gasket 3, membrane electrode assembly 4, deionized water 5, and water storage tank 6. During the test, H2 molecules come into contact with the sensing electrode surface of the membrane electrode assembly 4 through the gas diffusion vent 1, and the oxidation reaction shown in formula (1) occurs, producing protons (H2). + The electrons (e) are transported through the Nafion membrane of membrane electrode assembly 4 to the reference electrode and combine with oxygen to undergo the reduction reaction shown in equation (2) to produce water; wherein electrons (e) are transported through the Nafion membrane of membrane electrode assembly 4 to the reference electrode. - The transfer of current can only be achieved through an external circuit (an external circuit connecting the gas diffusion cap 2 and the water tank 6), which in turn generates current. The deionized water 5 in the water tank 6 provides a high-humidity environment for the Nafion membrane and ensures its high proton conductivity.
[0057] (1)
[0058] (2)
[0059] like Figure 5 As shown in (a), with the increase of the mass fraction of Pd metalene nanosheets, the current value of the sensor's external circuit shows a trend of first increasing and then decreasing. Among them, the 20 wt% Pdene / CF sensor has the highest current value (-159 μA), which is much greater than the current value of the 20 wt% PdNPs / CF sensor (-17 μA); Figure 5 As shown in (b), the sensitivity (i.e., the slope of the curve fitting the response current ΔI to the corresponding gas concentration) of the 5 wt% Pdene / CF sensor is -0.017 μA / ppm, and the linearity R0 is [missing value]. 2=0.999 (300~7500 ppm); the sensitivity of the 10 wt% Pdene / CF sensor is -0.037 μA / ppm, and the linearity R0 is 0.999 (300~7500 ppm); 2 =0.999 (300~7500 ppm); The sensitivity of the 30 wt% Pdene / CF sensor is -0.041 μA / ppm, and the linearity R0 is... 2 =0.999 (300~7500 ppm); The sensitivity of the 20 wt% PdNPs / CF sensor is -0.0084 μA / ppm, and the linearity R0 is... 2 =0.983 (300~7500 ppm); among them, the 20 wt% Pdene / CF sensor has the highest sensitivity (-0.052 μA / ppm) and excellent linearity (R0). 2 =0.999, 300~7500 ppm).
[0060] like Figure 6 As shown in (a), the current value of the sensor's external circuit quickly stabilizes with a step change in gas concentration, and maintains a monotonically increasing characteristic in the low to high concentration range, demonstrating good dynamic response characteristics. Figure 6 As shown in (b), the response time is 4 s and the recovery time is 2 s.
[0061] like Figure 7 As shown in (a), the six-cycle repeatability test curves demonstrate that the sensor has good continuous operating capability; Figure 7 As shown in (b), the sensor exhibits optimal selectivity for H2, with negligible response to common interfering gases; Figure 7 As shown in (c), the long-term stability test results of the 20 wt% Pdene / CF sensor (120 days) and the 20 wt% PdNPs / CF sensor (28 days) are presented. For the 20 wt% Pdene / CF sensor, its response current ΔI decreased by 12.6% and 37.6% from the initial value on the 7th and 14th days, respectively, and then tended to stabilize, with the response current ΔI remaining basically stable. In contrast, for the 20 wt% PdNPs / CF sensor, its response current ΔI decreased by 21.3% and 98.7% from the initial value on the 7th and 11th days, respectively, and then showed almost no response, indicating that the 20 wt% Pdene / CF sensor has good long-term stability.
Claims
1. A method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode, comprising the following steps: (1) Disperse Pd(acac)2 and W(CO)6 in a mixed solvent of DMF and acetic acid, and sonicate for 30-60 min to fully dissolve the solid and obtain the precursor solution; (2) The precursor solution obtained in step (1) is transferred to the reaction vessel, and the product Pd metal olefin nanosheets are obtained after the reaction. (3) The product obtained in step (2) is centrifuged and washed 5 to 10 times with anhydrous ethanol at a speed of 7000 to 9000 r / min, and the time for each centrifugation and washing is 5 to 10 min; then, the washed product is redispersed in anhydrous ethanol and then placed in a cell disruptor for ultrasonic dispersion treatment to obtain Pd metal olefin nanosheet suspension. (4) Disperse the pretreated carbon fibers in anhydrous ethanol, sonicate for 8-15 minutes, and continue stirring. During stirring, add the Pd metallene nanosheet suspension obtained in step (3) dropwise. Then continue stirring for 1-3 hours to ensure that the Pd metallene nanosheets are uniformly attached to the carbon fiber surface. Finally, dry in a vacuum oven at 50-70 °C for 10-12 hours. After grinding, obtain the Pdene / CF composite electrode. The mass fraction of Pd metallene nanosheets in the Pdene / CF composite electrode is 5-30 wt%. (5) Add 10-30 mg of the Pdene / CF composite electrode obtained in step (4) to a dispersant consisting of 100-120 μL of ethylene glycol, 200-240 μL of 5% Nafion solution and 400-480 μL of deionized water, and sonicate it to disperse it evenly to obtain a catalytic slurry; coat the catalytic slurry evenly on the surface of two flat polytetrafluoroethylene films, and dry them to obtain a sensitive electrode sheet and a reference electrode sheet with a Pdene / CF composite electrode layer on the surface; (6) Place the sensitive electrode sheet and the reference electrode sheet obtained in step (5) on both sides of the pretreated Nafion membrane and bond them together by hot pressing process, wherein the Pdene / CF composite electrode layers on the sensitive electrode sheet and the reference electrode sheet are both facing the Nafion membrane; after naturally cooling to room temperature, remove the polytetrafluoroethylene membranes on both sides of the Nafion membrane to obtain the membrane electrode assembly. (7) The gas diffusion cap, the membrane electrode assembly obtained in step (6), the isolation pad and the water tank are coaxially assembled from top to bottom. After being fixed and sealed, a room temperature fuel cell hydrogen sensor based on an ultrathin Pd metal olefin nanosheet / carbon fiber composite electrode is obtained.
2. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: The mass ratio of Pd(acac)2 to W(CO)6 is 1:2~4, and the volume ratio of DMF to acetic acid is 2~6:1; in the mixed solvent, the concentration of Pd(acac)2 is 0.001~0.005 mol / L, and the concentration of W(CO)6 is 0.0006~0.002 mol / L; the ultrasonic treatment temperature is <25 ℃.
3. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (2), the reaction conditions are to keep warm at 50~90 ℃ for 2~4h.
4. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (3), the ultrasonic power is 350~400 W and the ultrasonic time is 20~40 min.
5. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (4), the pretreatment of the carbon fiber involves sequentially bathing the carbon fiber in a 3%~9% volume fraction H2O2 aqueous solution, a 0.3~0.6 M H2SO4 aqueous solution, and deionized water at 70~90 ℃ for 0.5~1.5 h, and then taking it out and vacuum drying it at 60~80 ℃ for 6~12 h.
6. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (5), the thickness of the Pdene / CF composite electrode layer is 100~300 μm.
7. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (6), the temperature of the hot pressing process is 85~95 ℃, the pressure is 7~10 MPa, and the time is 60~150 s.
8. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (6), the Nafion membrane is pretreated by sequentially soaking it in a 3-9% (v / v) H2O2 aqueous solution, a 0.3-0.6 M H2SO4 aqueous solution, and deionized water in a water bath at 70-90 °C for 0.5-1.5 h, and then drying it.
9. The method for fabricating a room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode as described in claim 1, characterized in that: In step (7), the thickness of the membrane electrode assembly is 370~790 μm and the diameter is 5~20 mm; the thickness of the gas diffusion cap is 1~5 mm; the thickness of the isolation gasket is 0.2~1 mm; the height of the water tank is 10~60 mm; the diameter of the isolation gasket is similar to the diameter of the membrane electrode assembly, and both are smaller than the inner diameter of the water tank but larger than the outer diameter of the gas diffusion cap; the gas diffusion cap is made of stainless steel and has vent holes on its surface; the isolation gasket is made of stainless steel and has a micropore with a diameter of 0.5~3 mm in its center; the water tank is made of stainless steel and has an integrally formed annular boss near the top of its inner wall, and the isolation gasket is placed on the annular boss.
10. A room-temperature fuel cell-type hydrogen sensor based on an ultrathin Pd metallene nanosheet / carbon fiber composite electrode, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.
